Water Governance for Urban Resilience Analysis of Key Factors and the Role of Stakeholders in Metropolitan Area - Wahyu Mulyana; Emirhadi Suganda (The Indonesian Journal of Planning and Development, 2017)
Water governance is critical for water security and as enabling condition to achieve urban resilience. Water governance involves multi-actor, multi-sector and multi-level. Water governance system is the foundation for all stakeholders involved in water management in urban areas. Clarity of roles and responsibilities of each actor and coordination at all levels can help to meet the goals of urban water security to be more efficient, effective and inclusive. This article highlights the current water governance in a metropolitan area with level analysis on policy, organizational and operational. This is a multidisciplinary perspective of environmental science and public policy. Bandung Metropolitan Area (BMA) is chosen as a case study. Data and information gathered from secondary sources. The output is an initial baseline of water governance in BMA including key factors shaping water governance and role of stakeholder. This result will be used for the further research on dynamic and adaptive governance on the urban water sector.